The galleried Dun at Kildonan Bay, Kintyre - Fairhurst, Horace (Proceedings of the Society of Antiquaries of Scotland, 1939)
The dun is a substantial stone-built irregular oval structure. Four phases of occupation were identified (Kildonan I-IV). A paved single entrance way led into the structure. A twin staircase had been built into a portion of the northern wall. Occupation of the dun appears to have begun in the 2nd century or slightly earlier and continued into the 13th or 14th century.